1993
DOI: 10.1088/0029-5515/33/2/i01
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various physics phenomena on fast wave current drive in tokamaks

Abstract: The authors present an analysis of the influence of various physics phenomena (which are not necessarily independent) on current drive performance in tokamaks. Such phenomena include diffraction and other non-geometrical optics processes, k|| modification, and multiple-pass absorption as well as antenna characteristics such as recessed cavity and septa geometry, poloidal extent and poloidal location of the current straps. The two-and-one-half-dimensional (21/2-D) full-wave code PICES is used for modelling ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…General information about waves in plasmas can be found in Swanson's book (Swanson 2003) and Stix's book (Stix 1992); and the required Physics background on waves for heating plasmas and the early history of wave heating are available in (Cairns 1991). Reviews of electron cyclotron waves can be found in (Bornatici et al 1983), of lower-hybrid wave in (Bonoli 1985), and of ion cyclotron wave in (Jaeger et al 1993;Fuchs et al 1995;Wilson & Bonoli 2015). Having in mind the main elements of wave propagation and damping mechanisms, as well as the requirements for the ITER heating (Poli et al 2014), the method for modelling heating systems and the last physical phenomena to take in account following new experimental evidences will be presented.…”
Section: General Considerations On Wave Propagation For Plasmamentioning
confidence: 99%
“…General information about waves in plasmas can be found in Swanson's book (Swanson 2003) and Stix's book (Stix 1992); and the required Physics background on waves for heating plasmas and the early history of wave heating are available in (Cairns 1991). Reviews of electron cyclotron waves can be found in (Bornatici et al 1983), of lower-hybrid wave in (Bonoli 1985), and of ion cyclotron wave in (Jaeger et al 1993;Fuchs et al 1995;Wilson & Bonoli 2015). Having in mind the main elements of wave propagation and damping mechanisms, as well as the requirements for the ITER heating (Poli et al 2014), the method for modelling heating systems and the last physical phenomena to take in account following new experimental evidences will be presented.…”
Section: General Considerations On Wave Propagation For Plasmamentioning
confidence: 99%
“…To separate the fast waxe driven current from the other (4 Current 7 150 .... Figure 3 shows the experimentally determined rf driven current profile for 1.4 MW of injected rf power. Figure 3 also shows predictions from a model based on the ergodic limit of weakly damped rays (FASTCD) [6], a ray tracing code with multiple reflections ( C U~Y ) [7], and the results from full wave code (PICES) [8]. The experimentally determined non-inductive current profile due to FWCD and theoretical predictions from stochastic limit model and full wave code.…”
Section: Experimentally Determined Profiles Of Fast Wave Current Drivmentioning
confidence: 99%
“…The final match is made to a plasma impedance matrix which is generated by PLASMAIMP [7] or GLOSI[ 81 . RANT3D can also use its field solutions at the plasma interface as input to PICES [9], a 3D full wave plasma code used to calculate the detailed rf interaction with the target plasma.…”
Section: Numerical Codes Presently In Use At Ornlmentioning
confidence: 99%